Intersectional Stigma and Multi-Level Barriers to HIV Testing Among Foreign-Born Black Men From the Caribbean - Tonya N. Taylor; Jack DeHovitz; Sabina Hirshfield (Frontiers Media S.A., 2020)
Testing is the entry point into the HIV care continuum that includes linkage to and retention in prevention services, and adherence to prevention strategies, including repeat HIV testing. Despite US policy approaches to expand HIV testing to diverse clinical care and community settings, disparities in HIV testing among Black populations persist. Foreign-born (FB) Black persons from the Caribbean have higher annual rates of HIV diagnosis and a higher percentage of late-stage HIV diagnosis, compared with US-born Black persons; and most HIV infections among FB Blacks are among men. In this article, we provide an overview of HIV testing barriers among FB Black men who engage in HIV risk-taking behaviors (e.g., condomless sex with male and/or female partners of unknown HIV serostatus). Barriers to HIV testing for both FB and US-born Black men, include HIV stigma (anticipated, perceived, internalized), low perceived HIV risk, medical or government mistrust, and perceived low access to testing resources. We examine beliefs about masculinity and gender roles that may perpetuate heteronormative stereotypes associated with perceptions of low HIV risk and barriers to HIV testing. We also discuss the impact of recent immigration policies on accessing HIV testing and treatment services and how intersectional stigmas and structural forms of oppression, such as racism, prejudice against select immigrant groups, and homophobia that may further amplify barriers to HIV testing among FB Black men. Finally, we review comprehensive prevention approaches, and suggest innovative approaches, that may improve the uptake of HIV testing among FB Black men.